2022
DOI: 10.1111/jvim.16374
|View full text |Cite
|
Sign up to set email alerts
|

Serial analysis of blood biomarker concentrations in dogs with pneumonia, septic peritonitis, and pyometra

Abstract: Background Prolonged antimicrobial drug (AMD) treatment is associated with antimicrobial resistance development. Biomarker measurement may aid treatment decision‐making. Objectives Investigate temporal changes in blood biomarker concentrations in dogs undergoing treatment for pulmonary and intra‐abdominal infections; compare time to biomarker concentration normalization with duration of clinician‐directed AMD treatment. Animals Forty‐two client‐owned dogs with pneumonia (n = 22), septic peritonitis (n = 10), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 108 publications
(262 reference statements)
0
15
0
Order By: Relevance
“…Compared to the previous reports evaluating markers of disease recovery in dogs with pneumonia or aspiration pneumonia, this cohort of dogs is an older population, with many of the dogs having a more complicated clinical course due to their concurrent systemic or focal neuropathy. [21][22][23][24][25][26]28,38 The studies to date have primarily focused on cohorts of younger dogs, with reported median ages ranging from 5 to 5.5 years, and of the combined total of 46 dogs studied, only three dogs were described to have concurrent GLOPP (n = 1) or megaoesophagus (2). 21,22,24 This study population therefore represents a subpopulation of dogs at risk for A-ILI that is not well represented in the recent studies investigating acute-phase protein monitoring in dogs with aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the previous reports evaluating markers of disease recovery in dogs with pneumonia or aspiration pneumonia, this cohort of dogs is an older population, with many of the dogs having a more complicated clinical course due to their concurrent systemic or focal neuropathy. [21][22][23][24][25][26]28,38 The studies to date have primarily focused on cohorts of younger dogs, with reported median ages ranging from 5 to 5.5 years, and of the combined total of 46 dogs studied, only three dogs were described to have concurrent GLOPP (n = 1) or megaoesophagus (2). 21,22,24 This study population therefore represents a subpopulation of dogs at risk for A-ILI that is not well represented in the recent studies investigating acute-phase protein monitoring in dogs with aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as in people and recently investigated in dogs, after initiating treatment, the change in CRP concentrations over time rather than CRP normalisation may be more important, especially in patient populations with confounding clinical factors that could influence systemic inflammatory markers. 14,25 In people with acute respiratory infections, acute-phase protein-guided clinical algorithms have been used in many studies, targeting defined cut-off points or using the percent change in acute-phase protein concentrations. 14 For example, studies have reported using a greater than or equal to 80% reduction in acute-phase protein concentrations as a treatment endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Another study investigated other biomarkers including C-reactive protein and serum amyloid A in dogs with systemic infection including septic peritonitis and their concentrations decreased with treatment. 40 Other studies investigated biomarkers in peritoneal fluid including lactate, glucose and cytokines for diagnostic purpose. [41][42][43] It is, however, uncertain whether these biomarkers correlate with the severity of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple pathophysiologies of hyperlactatemia are possible in septic peritonitis, and it is unlikely that hyperlactatemia alone can correlate with the severity of peritonitis 39 . Another study investigated other biomarkers including C‐reactive protein and serum amyloid A in dogs with systemic infection including septic peritonitis and their concentrations decreased with treatment 40 . Other studies investigated biomarkers in peritoneal fluid including lactate, glucose and cytokines for diagnostic purpose 41–43 .…”
Section: Discussionmentioning
confidence: 99%